HOMOEOPATHIC MANAGEMENT OF OVARIAN CYST – A CASE REPORT - Arunava Nath*; Deb Kumar Palit; Nivedita Kundu (AYUSHDHARA, 2020)
Ovarian enlargements, cystic or solid, may occur at any age. Functional and inflammatory enlargements of the ovary develop almost exclusively during the childbearing years. They may be asymptomatic or produce local discomfort, menstrual disturbances, infertility, or in rare cases cause acute symptoms due to complications like haemorrhage, rupture or torsion. A case on dysmenorrhoea along with right ovarian cyst measuring about 52x45 mm has been presented which was treated with constitutional homoeopathic medicine Lycopodium clavatum. Literature review suggested spontaneous regression of cysts within 3 months with oral combined pills but in the presented case the subject had been suffering for last one year and was under hormonal treatment with no favourable results. In the case of simple cysts more than 5 cm in diameter and complex cysts, surgical removal of the mass is most often recommended in an attempt to preserve viable ovarian tissue. With homoeopathic approach the treatment lasted for nearly one year with gradual reduction in pain intensity and sonographically no detectable abnormality was noted after treatment.